Terbilang : potret tokoh wartawan negara - Chamil Wariya (Kuala Lumpur: Malaysian Press Institute, 2017)
Biography of Malaysian journalists
Includes index
Gift: Zainol Ahmad Resource Center
Gift: Prof. Dr. Md Sidin bin Ahmad Ishak
In Malay
Keywords: Journalism -- -- Malaysia; Journalists -- -- Malaysia